Histological Studies on a Newly Isolated Bacillus subtilis D10 Protease in the Debridement of Burn Wound Eschars Using Mouse Model - Ibtesam Al-Dhuayan; Essam Kotb; Amany Alqosaibi; Amal Mahmoud (MDPI AG, 2021)
Background: Proteases are among the most important industrial enzymes, playing a critical role in the physiological, biochemical, and regulatory processes of all living organisms. This study evaluated the histological effects of a Bacillus subtilis D10 protease in combination with the antibacterial ointment silver sulfadiazine (SSD) on the burned skin of mice. Materials and Methods: The bacterial proteolytic enzyme was produced and purified through DEAE-Sepharose CL-6B and Sephadex G-100 FF. The in vitro protease specificity was then determined. The dorsal skin of albino mice was burned with 80% HCl solution, then treated under three conditions: cold cream, SSD, and SSD combined with the tested protease. After 15 days of daily treatment, the mice were sacrificed and skin tissue samples were histopathologically examined using hematoxylin eosin, and Masson trichrome staining. Results: The D10 protease hydrolyzed the proteinaceous components of eschars (fibrin, normal collagen, and denatured collagen) in vitro. Mice skins treated with protease and SSD mixture showed promising results, with more rapid healing than the other treatments. This group regenerated epidermis and dermis with newly formed granulated follicles, fibroblasts and blood capillaries in the dermis, and collagen fibers in the hypodermis. Conclusions: These results suggest that the serine protease produced by B. subtilis D10 promotes wound healing of mice skin burnt with HCl and restores the normal architectural pattern in a shorter time than the standard treatments.